2019
DOI: 10.1016/j.cviu.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Domain invariant hierarchical embedding for grocery products recognition

Abstract: Recognizing packaged grocery products based solely on appearance is still an open issue for modern computer vision systems due to peculiar challenges. Firstly, the number of different items to be recognized is huge (i.e., in the order of thousands) and rapidly changing over time. Moreover, there exist a significant domain shift between the images that should be recognized at test time, taken in stores by cheap cameras, and those available for training, usually just one or a few studio-quality images per produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
0
31
1
3
Order By: Relevance
“…Although this method does not aim to predict the product categories, it can accurately perform the object proposal detection for the products with different scale ratios in one image, which is a practical issue in supermarket scenarios. In [ 71 ], authors considered three different popular CNN models, VGG-16 [ 42 ], ResNet [ 43 ], and Inception [ 70 ], in their approach and performed the K-NN similarity search extensively with the output of the three models. Their method was evaluated with three grocery product datasets, and the largest one contained 938 classes of food items.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method does not aim to predict the product categories, it can accurately perform the object proposal detection for the products with different scale ratios in one image, which is a practical issue in supermarket scenarios. In [ 71 ], authors considered three different popular CNN models, VGG-16 [ 42 ], ResNet [ 43 ], and Inception [ 70 ], in their approach and performed the K-NN similarity search extensively with the output of the three models. Their method was evaluated with three grocery product datasets, and the largest one contained 938 classes of food items.…”
Section: Techniquesmentioning
confidence: 99%
“…Although GANs have shown compelling results in the domains of general object classification and detection, there are very few works using GANs for product recognition. To the best of our knowledge, there are only three papers [ 7 , 71 , 78 ] attempting to exploit GANs to create new images in the field of product recognition. In the work of [ 7 ], the authors proposed a large-scale checkout dataset containing synthetic training images generated by CycleGAN [ 106 ].…”
Section: Techniquesmentioning
confidence: 99%
“…Therefore, research on identification of packaged products relies on relatively few, rather small and quite old datasets [9,17]. Existing studies on identifying packaged products via computer vision indicate promising potential [8,17,43,44], but they rely on such limited datasets and are conducted under resource-intense lab conditions, and do therefore not prove real-world applicability of computer vision based product identification. Although standards on product identifiers (e.g.…”
Section: Motivationmentioning
confidence: 99%
“…MR headsets such as Microsoft HoloLens or MagicLeap One are expected to be increasingly adopted by consumers in the near future and offer multiple advantage in supporting healthy food choices. For example, MR headsets feature multiple continuously active cameras that scan their nearby environment and can discover packaged products through computer vision without requiring active user input [40]. Such MR headsets also allow for the display of three-dimensional visualization of interventions, because spatial computing allows for relative positioning of visualizations to the user's field of view and detected objects, thereby achieving high degrees of presence, salience and immersion, important prerequisites for interventions.…”
Section: Motivationmentioning
confidence: 99%
“…MobileNet [34], ResNet [17], DenseNet [18]) or more recently, generative adversarial networks (GAN) [3]. Different, recent studies have demonstrated the feasibility to recognize packaged products through computer vision on a large scale from labelled images [14,26,39,40].…”
Section: Related Workmentioning
confidence: 99%